Islam Sebagai Sumber Hukum di Indonesia - Roby; Mustar; Surya Sukti (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Legal development in Indonesia is a complex process involving various issues, interests, and expectations. Islamic law has an important role in the formation of the national legal system as one of the recognized sources of law. However, the challenges faced in the integration of Islamic law with national law include the diversity of interpretations, harmonization with constitutional principles, and practical obstacles in implementation. This study uses a library method with a normative approach. The results of the discussion explain, namely, 1) The existence of Islamic law in Indonesia in the formation of legislation through the integration of religious norms into the current and future Indonesian national legal system using the Anglo-Saxon legal system model because the law will be applied to certain places, people and cases. 2) Islamic law has a strong influence in forming legal norms and values ​​in the national legal system. Islamic law in the legal system functions in three forms, first, Islamic law plays a role in filling the legal vacuum in positive law. Second, Islamic law contributes to the preparation of national law as a source of values. Third, Islamic law aims for rahmatan lil alamin, namely implementing and supervising its implementation in society.